Museum Transformation into Agents of Change: A Study for Building Youth Character in Jakarta - Asiz, Rangi Faridha (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The complex disruptions of the digital 4.0 era have minimized the youth’s role in contributing positively to development. Whereas, in the midst of global competition, that is vulnerable to hoaxes and weakens stability, their role is very much needed to encourage development and prevent national disintegration. Through its museums and historical sites, Jakarta can raise the spirits and role of young people because this city has a history as a symbol of nationalism and a meeting point for youth, which united the Indonesian nation during the independence era. The museum's potential is still hampered by a perception of exclusivity due to a lack of youth involvement in its activities. This is evident in the declining number of visitors, particularly among young people in Jakarta. To encourage young people's interest, the government needs to transform museums into agents of change, actively: 1) developing historical potential to transform the museum's function from